Mining entrepreneurship in the Kabardian (Nalchik) district in the 1870 s and 1880 s.: the case of the Freightman-Leev company - Timur, Dzuganov (Kavkazologiya, 2022)
The article examines the history of the first resource extraction enterprise in Kabardian (Nalchik) district in the post-reform period. In the coal's company example, Frechtman-Liev, the conditions of functioning of private entrepreneurship in the sphere of mining and processing of mineral re-sources are revealed, as well as the key moments that hindered the development of this industry. The revealed documents and materials allow to look in a new light at the specificity of realization of a private commercial initiative in the mining branch of the region, to realize the basic stages and the characteristic features of development of this direction of economy at a turn of XIX-XX centuries more deeply. Based on archival sources, determines the invalidity of theses about the negative role of “colonial policy” and “tsarist administration” as determinants of these processes. The negative role of the existing contradictions between the Caucasian administration, officials of the Mining Administration, and the Congress of the trustees of Kabarda and the Five Mountain Societies on the order of exploitation of mineral deposits on public lands is noted.